Arenavirus Induced CCL5 Expression Causes NK Cell-Mediated Melanoma Regression - Bhat, Hilal; Zaun, Gregor; Hamdan, Thamer A.; Lang, Judith; Adomati, Tom; Schmitz, Rosa; Friedrich, Sarah-Kim; Bergerhausen, Michael; Cham, Lamin B.; Li, Fanghui; Ali, Murtaza; Zhou, Fan; et al. (Frontiers in Immunology, 2020)
Immune activation within the tumor is one promising approach to induce immune-mediated tumor regression. Certain viruses including oncolytic viruses like herpes simplex virus (HSV) and non-oncolytic viruses such as lymphocytic choriomeningitis virus (LCMV) are potent tools to induce tumor-specific immune activation, however not all tumor types respond to viro- and/or immunotherapy and mechanisms explaining such differences remain to be defined. We used the non-cytopathic LCMV in different human melanoma tumor models and found that melanoma cell lines produced high levels of CCL5 in response to immunotherapy. In vivo, robust CCL5 production in LCMV infected Ma-Mel-86a tumor bearing mice led to recruitment of NK cells and fast tumor regression. Lack of NK cells or CCL5 as induced by the inhibitor Maraviroc abolished anti-tumoral effects of immunotherapy. In conclusion, we identified CCL5 and NK cell-mediated cytotoxicity as new factors influencing melanoma regression during virotherapy.